Assessing the Quality of the Management of Tonsillitis among Australian Children: A Population-Based Sample Survey. (January 2019) - Hibbert, Peter; Stephens, Jacqueline H.; de Wet, Carl; Williams, Helena; Hallahan, Andrew; Wheaton, Gavin R.; Dalton, Chris; Ting, Hsuen P.; Arnolda, Gaston; Braithwaite, Jeffrey
Objective: The aims of this study were twofold: (1) to design and validate a set of clinical indicators of appropriate care for tonsillitis and (2) to measure the level of tonsillitis care that is in line with guideline recommendations in a sample of Australian children. Study Design: A set of tonsillitis care indicators was developed from available national and international guidelines and validated in 4 stages. This research used the same design as the CareTrack Kids study, which was described in detail elsewhere. Setting: Samples of patient records from general practices, emergency departments, and hospital admissions were assessed. Subjects and Methods: Patient records of children aged 0 to 15 years were assessed for the presence of, and adherence to, the indicators for care delivered in 2012 and 2013. Results: Eleven indicators were developed. The records of 821 children (mean age, 5.0 years; SD, 4.0) with tonsillitis were screened. The reviewers conducted 2354 eligible indicator assessments across 1127 visits. Adherence to 6 indicators could be assessed and ranged from 14.3% to 73.2% (interquartile range 31.5% to 72.2%). Conclusion: Our main findings are consistent with the international literature: the treatment of many children who present with confirmed or suspected tonsillitis is inconsistent with current guidelines. Future research should consider how the indicators could be applied in a structured and automated manner to increase the reliability and efficiency of record reviews and help raise clinicians' awareness of appropriate tonsillitis management.